Optimization of extraction of lipid from Isochrysis galbana microalgae species for biodiesel synthesis. Issue 11 (3rd June 2017) - Silitonga, A. S.; Masjuki, H. H.; Ong, Hwai Chyuan; Mahlia, T. M. I.; Kusumo, F.
ABSTRACT: Microalgae are promising alternative plant sources for biodiesel production because of the signiﬁcant increase in lipid yield through heterotrophic cultivation and genetic engineering approaches. This study aims to evaluate the extraction and conversion of lipids from Isochrysis galbana . Response surface methodology (RSM) was used to optimize lipid extraction and thereby obtain high yields from the four microalgae species. The optimal lipid yields for Isochrysis galbana is 8.41 wt%. Moreover, the dominant lipid composition found from Isochrysis galbana extractions was palmitic acid (C16:0) at 22.3%. The high saturated acid of Isochrysis galbana contributed to the improved biodiesel properties because biodiesel quality is influenced by the lipid composition of microalgae species. The study employed the two-step esteriﬁcation–transesteriﬁcation process to convert the microalgae oil into biodiesel, glycerol, and water. The FAME content is 99.7% under the methanol to oil molar mass of 12:1, 1 wt%, 65°C, and 800 rpm. Furthermore, the main biodiesel properties, such as viscosity, higher heating value, and iodine value, were measured according to ASTM D6751 and EN 14124. Results show that microalgae oil can potentially be used as biofuel in future applications.